Criticality analysis of water network elements base on hydraulic simulations using the WNTR library - Antonowicz, Ariel; Urbaniak, Andrzej (Instal, 2022)
The article presents a proposal of an algorithm that determines the impact of the lack of individual elements of the water supply system on its proper functioning. Based on the base hydraulic model and configuration data, the algorithm automatically creates a set of sub-models. Then, after topological verification of subordinate models, hydraulic simulations are run, the results of which are saved directly to the indicated CSV file. Based on the results of the base simulation and the results of the sub-model simulation, the algorithm determines the suitability class of the analyzed element. The correctness of the developed and implemented method was verified on the example of a small water supply network.
Keywords: EPANET; WNTR; criticality analysis; classification of water network elements; hydraulic simulations